2010
DOI: 10.1007/s11483-010-9187-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physicochemical Modifications on Antioxidant Activity of Water-soluble Chitosan

Abstract: Water-soluble chitosan was processed using ultrasonication, microfluidisation and homogenisation to modify its physicochemical properties. The effect of using sonicated chitosan on formation of chitosan-glucose conjugates was investigated. Untreated and sonicated chitosan conjugates were prepared under varying reaction conditions (such as ratios of reactants, pH and temperature). The conjugates formed were evaluated for colour development and antioxidant activity. For both untreated and sonicated chitosans, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The native water-soluble chitosan showed low anti-oxidant activity when only 25.44% of activity was observed at 10 mg/mL; consequently, its IC 50 could not be detected. This result was similar to other reports, which reveal that the low anti-oxidant activity of chitosan and glucose-conjugate was one of the potential ways to enhance the anti-oxidant activity of chitosan [17,19,20]. The mechanics of anti-oxidant activity of glucose-conjugated chitosan may relate to its hydrogen donating capacity [19].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The native water-soluble chitosan showed low anti-oxidant activity when only 25.44% of activity was observed at 10 mg/mL; consequently, its IC 50 could not be detected. This result was similar to other reports, which reveal that the low anti-oxidant activity of chitosan and glucose-conjugate was one of the potential ways to enhance the anti-oxidant activity of chitosan [17,19,20]. The mechanics of anti-oxidant activity of glucose-conjugated chitosan may relate to its hydrogen donating capacity [19].…”
Section: Resultssupporting
confidence: 90%
“…Free radicals cause some serious damage in cells as well as tissues. The injurious effect of free radicals can be prevented or reduced by anti-oxidants [41], which include chitosan (in low molecular weight) and its derivatives [5,14,17,19,20,22,23]. Table 2 shows the anti-oxidant activity of WSCDs using DPPH radical scavenging assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the anti-oxidation properties of chitosan after the modification of Maillard reaction were remarkably improved as compared with chitosan or N-alkylation chitosan derivative. To date, the majority of studies focused on Maillard reaction of chitosan with such mono-saccharides as glucose (Rao et al, 2011;Weerakkody, Labbett, Cheng, & Kosaraju, 2011) and fructose (Dong et al, 2014;Ying, Xiong, Wang, Sun, & Liu, 2011). Because of different chemical structure between mono-saccharides and disaccharides, it was expected that the MRPs from disaccharide and chitosan would display varying antioxidant activity from those from mono-saccharide and chitosan.…”
Section: Introductionmentioning
confidence: 99%